Determination Determination of Loss Macro Nutrient (N, P And K) Carrying Out The Harvest of Arabika Coffee Fruits (Coffea Arabica) In Five Locations of Situbondo Coffee Farmers - Wulanjari, Distiana; Rosyady, Muhammad Ghufron; Felda Afrizal Putra; Ketut Anom Wijaya; Hasbi Mubarak Suud; Oria Alit Farisi (Journal of Soilscape and Agriculture, 2023)
The coffee plant (Coffea sp.) is one of the plantation commodity crops that has been developed since the Dutch colonial era. The productivity of Arabica coffee from people's fields is equal to 0.48 tons/ha while the company's Arabica coffee plantations 0.71 tons/ha. Low productivity is one of them caused by fertilization that is not in accordance with the needs of coffee plants. So, it is necessary to know the nutrient content of N, P and K in each plantation. The content of N, P and K nutrients can be determined through the development of fertilization methods based on the loss of N, P and K nutrients carried by the harvested coffee cherries. The aim of this research is to find out of N, P and K nutrients are carried by Arabica coffee berries. The treatment was carried out at 5 different coffee fields locations and an analysis of the N, P, and K nutrient content of the harvested coffee cherries was carried out. The results showed that the nutrients N, P, and K carried by the coffee cherries were different in each plantation. Soil Analysis results on pH (bit acid) and Total Nutrient Content N (low), P (moderate – very high), and K  (low) in the soil of each field. The variables for observing the weight of sun-dried coffee beans and skins and the weight of oven-dried coffee beans and skins were significantly different in each plantation. Conclusions from this research, a). The total N, P, and K contained in 1 kg of fresh coffee fruit is 24.71 g N; 8.66 g P and 39.08 g K. b). The total N, P, and K contained in 1 kg of dry coffee beans is 74.3 g N; 26.1 g P and 117.5 ​​g K.